DEVELOPMENT AND VALIDATION OF ULTRAVIOLET-SPECTROPHOTOMETRIC METHOD FOR DETERMINATION OF FEBUXOSTAT FOR CONDUCTING IN-VITRO QUALITY CONTROL TESTS IN BULK AND PHARMACEUTICAL DOSAGE FORMS - Kaur, Jaspreet; Kaur, Daljit; Singh, Sukhmeet (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple, accurate, and selective ultraviolet-spectrophotometric method has been developed for the estimation of febuxostat in the bulk and pharmaceutical dosage forms. Method: The method was developed and validated according to International Conference on Harmonization (ICH Q2 R1) guidelines. The developed method was validated statistically with respect to linearity, range, precision, accuracy, ruggedness, limit of detection (LOD), limit of quantitation (LOQ), and recovery. Specificity of the method was demonstrated by applying different stressed conditions to drug samples such as acid hydrolysis, alkaline hydrolysis, oxidative, photolytic, and thermal degradation. Results: The study was conducted using phosphate buffer pH 6.8 and Î»max was found to be 312 nm. Standard plot having a concentration range of 1â€“10 Î¼g/ml showed a good linear relationship with R2=0.999. The LOD and LOQ were found to be 0.118 Î¼g/ml and 0.595 Î¼g/ml, respectively. Recovery and percentage relative standard deviations were found to be 100.157Â±0.332% and <2%, respectively. Conclusion: Proposed method was successfully applicable to the pharmaceutical formulations containing febuxostat. Thus, the developed method is found to be simple, sensitive, accurate, precise, reproducible, and economical for the determination of febuxostat in pharmaceutical dosage forms.